SOL–POV - Lee, Frederick Jih Xuan (Nanyang Technological University, 2021)
SOL – POV stems from the concept of solace, soul and perspective. Music album packaging contains the soul fed by music, which provides solace to listeners. Fresh perspectives will include personal stories relating to music, and these are shared by 15 Singaporean listeners age 22-27.